Mechanism for Preventing Shariah Non-Compliance (SNC)Events in Islamic Financial Institutions - Muhammad Ridhwan Ab. Aziz; Noor Naemah Abdul Rahman (Penerbit UIS, 2024)
VOL.10 NO.2(SEPTEMBER 2023) (Page : 197-208)